Biomechanical differences of the technical gesture of the free half squat in professional and amateur bodybuilders/Diferencias biomecánicas del gesto técnico de la media sentadilla libre en físico-culturistas profesionales y amateur - Michael Alexander Moreno Martínez; Leonardo Andrés Romero Acosta; Leonardo Xavier Quintanilla Ayala (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2022)
The improvement of the sports technique is premised on comparing the values of the motor movement, this must be characterized to correct errors detected as part of the sports training management process. Emphasis is placed on highly technical sports, such as bodybuilding training. In this sense, the present research aimed to analyze the half-squat technique in professional and amateur bodybuilders as an empirical method (sport-specific measurement). The research is descriptive-explanatory of correlational order. Six variables of interest are correlated (X1: shoulder joint angle; X2: hip joint angle; X3: maximum speed reached; X4: maximum acceleration reached; X5: center of gravity in X; X6: center of gravity in Y). The means establish differences between independent groups, both in variable X1 (Group 1: ≈66°; Group 2: ≈70°; p=0.247 ), X2 (Group 1: ≈73°; Group 2: ≈86°; p=0.002 ), X3 (Group 1: ≈1.03m/s; Group 2: ≈1.36m/s; p=0.017 ), X4 (Group 1: ≈2.93m/s 2 ; Group 2: ≈4.78m /s 2 ; p=0.011 ), X5 (Group 1: ≈0.43m; Group 2: ≈0.65m; p=0.000 ), and X6 (Group 1: ≈0.61m; Group 2: ≈0.83m; p =0.000 ). Group 1 has a more effective technique, while the amateurs have less efficiency in biomechanical movement due to their inexperience, high values are shown in speed and acceleration, movement angles such as hip angles are included.